Gamified VS Non-gamified Speaking Assessment for EFL in Higher Education - Yudi Basuki (AL-ISHLAH: Jurnal Pendidikan, 2023)
Students of the eighth basic level must have an A1 level. After developing their speaking skills, a speaking assessment needs to be given to students in the class to know how good their speaking skills are. This research aimed to compare the gamified and non-gamified speaking assessments to the speaking scores of students. This research used an experimental design with a quantitative approach. The participants of this research were the students of STKIP PGRI Trenggalek English Language Learning Students chosen by purposive sampling technique. The instrument of this research used pre and post-test to determine the increase and difference between the two groups. The data collected were analyzed using SPSS software. The results showed that when the students’ speaking skill was assessed utilizing gamified speaking assessment, it was easier for students to increase their score. This research result could provide a contribution to the basic literature on utilizing gamified speaking assessments to motivate students. Thus, they can enhance their speaking skill, leading to an increased speaking score.